Cloud based smart parking system using IoT technology - Rahman, Zubydur; Hossain, Ahmed Tanzeer; Karim, Nibras Abdullah; Jayeed, Mohammad (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.